The Concept of Parenting Patterns In Education of Children's Moral Values - Purnamasari, Rika (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
Moral education is a process of forming children through sound processes and coaching from various elements of society. Moral education will not be appropriately realized without the process of understanding the cognitive, affective, and psychomotor of children through the guidance of parents as first educators. The purpose of this study was to find the concept of parenting in educating children's morals. The research method uses qualitative. Sources of data are journals, books, research results, encyclopedias, and other relevant literature. Fundamental analysis by reading, analyzing, and finding relevant literature patterns. Analysis technique with thesis, antithesis, and synthesis of the literature on parenting patterns of parents in educating children's morals. The study results can be used as a reference for further research on research themes related to parenting patterns in educating children's morals.